ASSOCIATION BETWEEN RUKUK PRAYER POSITION AND LOWBACK PAIN AMONG LECTURERS IN THE FACULTY OF MEDICINE,UNIVERSITAS MUSLIM INDONESIA. - R.H, ANDI NUR AMALIAH (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2026)
Background: Low back pain (LBP) is a common musculoskeletal disorder that limits daily activities and reduces productivity. Rukuk, a bowing position performed during Islamic prayer, requires correct spinal alignment. Incorrect posture can increase the risk of LBP, but empirical evidence is still limited. Objective: This study aims to examine the relationship between the rukuk position and the severity of low back pain among medical faculty lecturers. Methods: A cross-sectional study was conducted on 71 female lecturers at the Faculty of Medicine, Indonesian Muslim University, selected through simple random sampling. Data were collected using the Aberdeen Low Back Pain Scale questionnaire and structured interviews. Descriptive statistical analysis and Chi-square correlation tests were performed using SPSS software. Results: Most respondents were in the productive age category (83.1%). Proper bowing posture was observed in 91.5% of respondents. Mild low back pain was reported by 83.1%, 9.9% experienced moderate low back pain, while 7.0% experienced severe low back pain. Chi Square correlation analysis showed a significant relationship between bowing posture and the severity of low back pain (p = 0.02). Conclusion: Most lecturers performed rukuk correctly and only reported mild lower backpain. This study found a significant relationship between rukuk posture and back pain. Further research with a larger and more diverse population, as well as a longitudinal design, is recommended to better understand the potential relationship between religious practices, posture, and musculoskeletal health.